I Do It, but I Decide With Whom - Pulido, Cristina M.; Vidu, Ana; Racionero-Plaza, Sandra; Puigvert, Lídia (Frontiers in Psychology, 2021)
Social interactions and communication shape the desires and preferences of men and women. While it is true that some men have modified their behavior due to feminist women, the same happened with some women, who changed attraction patterns thanks to new alternative masculinities (NAM). This study examines the latter, focusing on social interactions mediated by language, as a crucial element to impact and change the desires of people. For this purpose, six autobiographical interviews were conducted with women aged 19–39 years, from two different countries and continents, paying attention to the narratives of their sexual-affective relationships. Using the communicative methodology, interactions have been analyzed from verbal communication and nonverbal communication, based on the consequences of the actions rather than intentionality. The results of this study show how dialogic communicative acts with NAMs influenced some women who first defended or justified actions of male perpetrators to later prefer to support female survivors against their perpetrators. Analysis reveals that communicative acts grounded in such language that enacted the desire of NAM for women of solidarity have shaped some memories of women of relationships with dominant traditional masculinities (DTM) and, ultimately, contributed to change their attraction and election patterns.